Identifying Crowding Stress‐Tolerant Hybrids in Processing Sweet Corn. (1st September 2015) - Williams, Martin M.
Abstract : Improvement in tolerance to intense competition at high plant populations (i.e., crowding stress) is a major genetic driver of corn ( Zea mays L.) yield gain the last half‐century. Recent research found differences in crowding stress tolerance among a few modern processing sweet corn hybrids; however, an investigation of interactions with other factors would reveal a deeper understanding of crowding stress tolerance in sweet corn. The objectives of this study were to (i) compare yield, recovery, and processor profitability of sweet corn hybrids grown under conditions of crowding stress, and (ii) determine if an interaction exists between N fertilization and hybrid on crop response to crowding stress. Twenty‐six hybrids were grown under suboptimal and supraoptimal N fertilization at 72, 000 plants ha −1, a level beyond the optimal population of the most crowding stress‐tolerant hybrid. Results showed hybrid and N fertilization had no interactive effect on key variables of interest to the sweet corn processing industry, namely green ear mass, recovery, case production, and gross profit margin. Therefore, hybrid rankings were consistent whether the crop was N stressed or not. Relative to the poorest performing hybrid, the highest performing hybrid grown at an elevated population yielded 50% more green ear mass, 61% greater case production, and 71% higher gross profit margin. This work demonstrated a simple method to identify processing sweet corn hybrids with the best tolerance to crowding stress. Significant gains in sweet corn productivity may be realized by growing such hybrids at plant populations higher than currently used.